The Impact of Urban Pollution on Plasmid-Mediated Resistance Acquisition in Enterobacteria from a Tropical River - Bradd Mendoza-Guido; Kenia Barrantes; César Rodríguez; Keilor Rojas-Jimenez; Maria Arias-Andres (MDPI AG, 2024)
Background: The exposure of environmental bacteria to contaminants in aquatic ecosystems accelerates the dissemination of antibiotic-resistance genes (ARGs) through horizontal gene transfer (HGT). Methods: In this study, we sampled three locations along a contamination gradient of a polluted river, focusing on isolating Enterobacteria from the surface waters to investigate the relationship between urban pollution and antibiotic resistance. The genomes of 15 isolates (5 per site) were sequenced to identify plasmid-borne ARGs and their association with resistance phenotypes. Results: Isolates from the site with the highest contamination (Site 3) showeda larger number of ARGs, plasmids, and resistance phenotypes. Notably, one of the isolates analyzed, E. coli A231-12, exhibited phenotypic resistance to seven antibiotics, presumably conferred by a single plasmid carrying 12 ARGs. Comparative analysis of this plasmid revealed its close evolutionary relationship with another IncH plasmid hosted by Salmonella enterica, underscoring its high ARG burden in the aquatic environment. Other plasmids identified in our isolates carried sul and dfrA genes, conferring resistance to trimethoprim/sulfamethoxazole, a commonly prescribed antibiotic combination in clinical settings. Conclusions: These results highlight the critical need to expand research on the link between pollution and plasmid-mediated antimicrobial resistance in aquatic ecosystems, which can act as reservoirs of ARGs.